2006
DOI: 10.1038/sj.cdd.4402038
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory caspases and inflammasomes: master switches of inflammation

Abstract: Fifteen years have passed since the cloning and characterization of the interleukin-1b-converting enzyme (ICE/caspase-1), the first identified member of a family of proteases currently known as caspases. Caspase-1 is the prototypical member of a subclass of caspases involved in cytokine maturation termed inflammatory caspases that also include caspase-4 caspase -5, caspase -11 and caspase -12. Efforts to elucidate the molecular mechanisms involved in the activation of these proteases have uncovered an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
601
0
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 722 publications
(627 citation statements)
references
References 139 publications
8
601
0
11
Order By: Relevance
“…The inactive IL1b precursor requires enzymatic cleavage to an active cytokine by the intracellular cysteine protease, caspase-1. Caspase-1 represents the central effector protein of the inflammasome, a cytosolic multi-protein complex that functions as molecular scaffold for caspase activation [45]. Even though it has been widely demonstrated that galectin-3 induces proinflammatory reactions, no relationship between this molecule and the inflammasome complex has been demonstrated so far.…”
Section: Discussionmentioning
confidence: 99%
“…The inactive IL1b precursor requires enzymatic cleavage to an active cytokine by the intracellular cysteine protease, caspase-1. Caspase-1 represents the central effector protein of the inflammasome, a cytosolic multi-protein complex that functions as molecular scaffold for caspase activation [45]. Even though it has been widely demonstrated that galectin-3 induces proinflammatory reactions, no relationship between this molecule and the inflammasome complex has been demonstrated so far.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although inflammasome components such as NALP3 and ASC are central for caspase-1 activation, this process does not necessarily require activation by microbial products in human monocytes. This is in contrast with the literature from which the concept was proposed that inflammasome activation by danger molecules (either bacterial or not) is an essential step for the induction of IL-1b production [44]. However, this concept has been built upon a body of evidence derived from monocyte/macrophage cell-lines (e.g.…”
mentioning
confidence: 86%
“…The absence of a genetic mouse model that specifically blocks pyroptosis considerably limits our ability to delineate pyroptosis functions in vivo. Moreover, discrepancies between the immune systems of humans and mice [49], for example the low evolutionary similarity within inflammatory caspases [12], limit our full understanding of pyroptosis in human health and disease. This highlights the necessity for future research examining pyroptosis mechanisms and functions in a context clearly relevant for humans and the pathogens to which we are exposed.…”
Section: Resultsmentioning
confidence: 99%